FROM GENETICS TO CLINICAL PRACTICE: APPLICABILITY OF POLYGENIC RISK IN CORONARY ARTERY DISEASE (CIPEEX, 2025)
Introduction: According to the Brazilian Society of Cardiology, Coronary Artery Disease (CAD) is characterized by partial or total obstruction of blood flow through the coronary arteries, usually due to atherosclerosis, and is one of the leading causes of morbidity and mortality worldwide. Therefore, CAD has a multifactorial etiology, involving traditional risk factors and environmental factors. Furthermore, the role of genetic inheritance in CAD susceptibility has been demonstrated. Thus, polygenic risk scores (PRSs) represent the sum of multiple common genetic variants that can predispose to the development of a given disease. In that regard, this presents a promising strategy for developing personalized strategies to prevent or diagnose specific pathologies early. This extract analyzes how PRSs can improve the prediction and prevention of CAD, positively impacting the costs and adverse effects associated with the disease.Objective: To analyze how polygenic risk can improve the prediction and prevention of coronary artery disease, analyzing how this concept can be applied in clinical practice.Methodology: This is a simple summary, using the ScienceDirect, National Library of Medicine (PubMed), and Virtual Health Library (VHL) databases. For the literature search, the following Health Sciences Descriptors were used: Coronary Artery Disease; Genetic Risk Score; Risk Factors; and Genome, Human. These were combined using the Boolean operator "AND." Based on this, 6,224 articles were found. From this, 6,224 articles were found and, after applying the inclusion criteria, last 5 years: 2,864; full text available for free: 1,407; and the exclusion criteria: type of study: 214; reading of the title and abstract: 32; and those that responded to the objective: 5.Results: Identifying individuals at high risk of developing CAD is crucial, as it allows for the implementation of primary prevention strategies. In this regard, high PRS values ​​have been associated with a significantly increased risk of CAD. Furthermore, identifying young individuals with an extremely high PRS, before the occurrence of clinical manifestations, may be beneficial for implementing early interventions in clinical practice, such as the use of statins and intensive lifestyle changes, preventing the occurrence of a first CAD event. Furthermore, the combined PRS has been shown to be a more reliable predictor of CAD compared to several well-established risk factors, including high cholesterol and hypertension. Despite this, PRS does not take into account key factors involved in the development of a disease, such as environmental influences. Then, PRS cannot replace traditional risk factors in predicting the likelihood of CAD.Conclusion: Therefore, polygenic risk scores represent a promising advance in coronary artery disease risk stratification, complementing traditional models, especially in younger and intermediate-risk populations. In this regard, they contribute to the implementation of personalized prevention, enhancing early interventions. Despite this, limitations remain, particularly regarding population diversity, ethics, and practical feasibility.
Keywords: Coronary Artery Disease; Genetic Risk Score; Risk Factors; Genome, Human